2011
DOI: 10.1200/jco.2010.31.2405
|View full text |Cite
|
Sign up to set email alerts
|

SLCO2B1 and SLCO1B3 May Determine Time to Progression for Patients Receiving Androgen Deprivation Therapy for Prostate Cancer

Abstract: A B S T R A C T PurposeAndrogen deprivation therapy (ADT), an important treatment for advanced prostate cancer, is highly variable in its effectiveness. We hypothesized that genetic variants of androgen transporter genes, SLCO2B1 and SLCO1B3, may determine time to progression on ADT. Patients and MethodsA cohort of 538 patients with prostate cancer treated with ADT was genotyped for SLCO2B1 and SLCO1B3 single nucleotide polymorphisms (SNP). The biologic function of a SLCO2B1 coding SNP in transporting androgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
148
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 30 publications
7
148
3
Order By: Relevance
“…Consistent with findings reported by Hamada and colleagues (2), Sharifi and colleagues (3), and Yang and colleagues (4) in studies of men with advanced prostate cancer receiving androgen deprivation therapy (ADT), we show that a high-testosterone import allele of SLCO1B3 SNP rs4149117 is also associated with an increased risk of prostate cancer-specific mortality (PCSM) in a population-based study of incident prostate cancer cases. Although the associated HRs in each study are small, the consistency of the observation is striking given the differences in the prostate cancer populations under evaluation.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with findings reported by Hamada and colleagues (2), Sharifi and colleagues (3), and Yang and colleagues (4) in studies of men with advanced prostate cancer receiving androgen deprivation therapy (ADT), we show that a high-testosterone import allele of SLCO1B3 SNP rs4149117 is also associated with an increased risk of prostate cancer-specific mortality (PCSM) in a population-based study of incident prostate cancer cases. Although the associated HRs in each study are small, the consistency of the observation is striking given the differences in the prostate cancer populations under evaluation.…”
supporting
confidence: 78%
“…As discussed by Figg and colleagues in their letter, our work and the work by Yang and colleagues (4) reported different findings for the SLCO2B1 SNP rs12422149 [which encodes for a dehydroepiandrosterone (DHEA) sulfate (DHEAS) transporter]. Whereas Yang and colleagues observed a more rapid time to progression on ADT in men bearing a high-DHEAS import allele of SLCO2B1 SNP rs12422149, we observed an increased risk of PCSM in men bearing the lowimport allele.…”
contrasting
confidence: 54%
“…Recent studies have suggested that functional genetic polymorphisms in the CYP19A1 gene may modify serum and/or intratumoral sex hormone levels and therefore influence prostate cancer risk and survival (Latil et al 2001, Suzuki et al 2003, Tsuchiya et al 2006, Kanda et al 2015. The androgen transporter gene SLCO2B1 also has a polymorphism that has been associated with prostate cancer risk and outcome (Yang et al 2011). While none of these associations are incredibly strong, taken together, these findings suggest androgen pathway genes likely influence prostate cancer risk, suggesting that androgens are involved in tumorigenesis.…”
Section: Ar In Prostate Cancer Initiationmentioning
confidence: 55%
“…In advanced disease state, studies have shown the impact of HSD17B4 genetic variations (13) and expression (14) relative to disease progression, and germline variations in SLCO2B1 and SLCO1B3 in response to palliative ADT therapy (15). However, there is still a lack of molecular markers better defining aggressive and lethal prostate cancer.…”
Section: Authors' Affiliationsmentioning
confidence: 99%